2012
DOI: 10.1093/nar/gks1274
|View full text |Cite
|
Sign up to set email alerts
|

Competing roles of DNA end resection and non-homologous end joining functions in the repair of replication-born double-strand breaks by sister-chromatid recombination

Abstract: While regulating the choice between homologous recombination and non-homologous end joining (NHEJ) as mechanisms of double-strand break (DSB) repair is exerted at several steps, the key step is DNA end resection, which in Saccharomyces cerevisiae is controlled by the MRX complex and the Sgs1 DNA helicase or the Sae2 and Exo1 nucleases. To assay the role of DNA resection in sister-chromatid recombination (SCR) as the major repair mechanism of spontaneous DSBs, we used a circular minichromosome system for the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 68 publications
(52 reference statements)
2
10
1
Order By: Relevance
“…As expected, we observed a deviation of the balance towards an increase of homology-mediated repair (Figure 4, Tables S2 and S3). These results agree with previously published reports that indicate that, in the absence of NHEJ, DNA-end are unprotected, resection occurs, and the breaks are more prone to be repaired by homologous recombination [5], [16][21]. Although we observed a similar trend for both SSR 1.0 and 2.0, it was clearer in the latter (Figure 4).…”
Section: Resultssupporting
confidence: 93%
“…As expected, we observed a deviation of the balance towards an increase of homology-mediated repair (Figure 4, Tables S2 and S3). These results agree with previously published reports that indicate that, in the absence of NHEJ, DNA-end are unprotected, resection occurs, and the breaks are more prone to be repaired by homologous recombination [5], [16][21]. Although we observed a similar trend for both SSR 1.0 and 2.0, it was clearer in the latter (Figure 4).…”
Section: Resultssupporting
confidence: 93%
“…It is likely that these yku mutants exhibit reduced affinity for DNA ends, as do those described by Petrini and colleagues 40 . If the basis of suppression of sae2D sgs1Dmutant phenotype by yku mutations is to restore end resection by allowing Exo1 access to DSBs arising during DNA replication 36,37,40,41 , then the rescue should be dependent on HR. We found that deleting RAD52 reduced the size of the sae2D sgs1D yKu70D spore colonies ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, rpb1‐S751F was tolerated in both rad51∆ and pol32∆ backgrounds. As we have previously shown that Rad51 and Pol32 control two overlapping outcomes of Rad52‐dependent HR events (Moriel‐Carretero & Aguilera, ; Muñoz‐Galván et al , ), we tested whether rpb1‐S751F rad51∆ pol32∆ triple mutants were viable or not. Indeed, they were not, suggesting that these mutants accumulate replication‐born DNA breaks that cannot be repaired in the absence of Rad51 and Pol32.…”
Section: Resultsmentioning
confidence: 99%